Is Genetic Discrimination Back on the Radar? A Commentary on the Recent Court of Appeal Reference Decision on the Genetic Non-Discrimination Act (GNDA) - Joly, Yann; Dalpé, Gratien; Pinkesz, Miriam (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2019)
In this commentary, we critically review the Quebec Court of Appeal’s reference decision to the effect that the Genetic Non-Discrimination Act (GNDA) is unconstitutional. In sum, the court held that the federal government exceeded its criminal law power through the GNDA, as the Act did not have a valid criminal law purpose. The decision was met with opposition, as advocacy groups for Canadians suffering from genetic diseases or genetic predispositions viewed the GNDA as a step in the right direction and were hopeful that it would offer protection from genetic discrimination. In closing, we argue that the consequences of the Court of Appeal’s opinion will be less dire than anticipated by some advocacy groups. In fact, we suggest that this decision brings about a unique opportunity for progress, where stakeholders can engage the public and policymakers in a forward- looking debate on the use of genetic information.